Study of coccidiosis of scavenging indigenous chickens in central Ethiopia - Ashenafi, H.; Tadesse, S.; Medhin, G.; Tibbo, Markos (Springer, 2004)
An investigation was made into coccidiosis of 190 scavenging indigenous chickens between September 2000 and April 2001 in three selected agroclimatic zones, in central Ethiopia. This was done through clinical, postmortem and microscopic examinations. Data were processed by chi-square and Mantel–Haenzel test. The study indicated that 25.8% (49/190) of the chickens were infected with coccidiosis and found to harbour one to four different species of Eimeria. Of these infected chickens, 30 (15.8%) and 19 (10.0%) were positive for clinical and sub-clinical coccidiosis, respectively. There was a significant altitude difference ( 2 = 14.7, p<0.001) in coccidiosis prevalence: 42.2% in chickens from highland region followed by 21.5% in mid-altitude and 13.1% in low-altitude areas. When quantified, the prevalence of coccidiosis was 2.66 and 4.83 times higher in the high-altitude than in mid-altitude (odds ratio, OR = 2.66, p<0.05) and low-altitude (OR = 4.83, p<0.001) chickens. The pathogenic Eimeria species responsible for clinical coccidiosis were E. necatrix, E. acervulina, E. maxima and E. tenella. With increasing demand for poultry products in developing countries, knowledge of production constraints in traditional management practices could help devise control strategies for constraints on backyard poultry production systems.